Market Penetration Strategy through Social Media Marketing to Create Consumer Loyalty - Gema Merdeka Goeyardi; Dessy Rahayu Ramadhasari; Arasy Alimudin (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: To analyze how much influence price, sales discount and brand awareness have on consumer loyalty at Rustic Market Café Surabaya, either partially or simultaneously. Design/methodology/approach: In this study using a quantitative research approach. The sample used in this study were 100 respondents who had visited the Rustic Market Café Surabaya. The sampling technique used is non-probability sampling (purposive sampling). The data collection tool uses a questionnaire. Analysis of the data used is Multiple Linear Regression Test and Hypothesis Testing using SPSS 18. Findings: The results of the partial study, the data showed that there was a partially insignificant effect between the price variable (X1) on Consumer Loyalty (Y) with a significance value of 0.068. The Sales Discount Variable (X2) on Consumer Loyalty (Y) shows a partially significant effect with a significance value of 0.003. The Brand Awareness (X3) variable on Consumer Loyalty (Y) shows a partially significant effect with a significance value of 0.000. Simultaneous research results, the data shows a significant effect simultaneously with a significance value of 0.000. Thus it can be concluded that the variables consisting of Price (X1), Sales Discounts (X2), and Brand Awareness (X3) have a significant simultaneous effect on the Consumer Loyalty variable (Y). Paper type: Research paper